Balancing GHG mitigation and food security through agricultural recycling systems: Case studies in the North China Plain. (20th July 2017) - Li, Zhejin; Sui, Peng; Yang, Xiaolei; Dai, Hongcui; Wang, Xiaolong; Long, Pan; Yan, Lingling; Chen, Yuanquan
Abstract: In recent years, China has developed a series of disposal methods and corresponding recycling systems to deal with agricultural wastes, as well as to mitigate climate change. The objective of this paper is to evaluate the net greenhouse gas emissions (NGHGE) and crop yields of three types of typical recycling systems, based on case studies in the North China Plain. These systems are the CC system, "crop production-crop production" by returning crop straw to the soil; CPC system, "crop production-pig rearing-crop production" by returning pig manure to the soil; and the CPBC system, "crop production-pig rearing-biogas production-crop production" by returning biogas residue to the soil. The overall results show that a reduction of 15.18% in NGHGE was achieved with the CPC system compared with a system where no pig manure was returned to the soil. NGHGE of CPBC system achieved a reduction of 352.25% compared with no biogas being produced and no pig manure being returned. These results imply that the development of recycling agriculture, i.e., manure reuse and biogas production, is a superior method to reduce GHG emissions. Additionally, compared with CC system, crop yields improved by 17.75% and 18.68% in the CPC and CPBC systems, respectively, which is an important factor in guaranteeing food security. Therefore, compared with non-recycling practices, by reusing organic wastes, these recycling systems reduced the total GHG emissions and increased crop yields. Accordingly, agricultural recycling offers a promising system for dealing with large volumes of waste, responding to global climate change, and ensuring food security in China. Highlights: Net GHG emissions and grain yields of different recycling systems were evaluated. Both GHG emissions and carbon sequestrations were taken into consideration. Recycling systems reduced more GHG emissions than non-recycling systems. Recycling systems increased crop yield through organic wastes reused. Recycling systems help China address climate change and ensure food security.